Exposure assessment of ultrafine particles in epidemiologic time-series studies - Pekkanen, Juha; Kulmala, Markku (Scandinavian Journal of Work, Environment & Health, 2004)
The health effects of fine-particulate air pollution (PM2.5, aerodynamic diameter <2.5 µm) observed in epidemiologic time-series studies may partly be due to the high number concentration of ultrafine particles (aerodynamic diameter <0.1 µm) in urban air. The key uncertainty is how well daily variations in the ultrafine particle concentration measured at a central site correlate with the variations in average personal exposure. Due to a lack of research data, this correlation has been estimated indirectly in this review on the basis of studies on the sources, ambient air levels, spatial variability, indoor air levels, and lung deposition of ultrafine particles. It is concluded that central site monitoring may give a somewhat worse proxy for human exposure to ultrafine particles than to PM2.5 in time-series studies.
Keywords: epidemiology; exposure; exposure assessment; indoor air; indoor-to-outdoor ratio; particle mode; particulate matter with an aerodynamic diameter of; review; time-series study; ultrafine particle; urban air